Monomeric and dimeric 68Ga-labeled bombesin Analogues for Positron Emission Tomography (PET) imaging of tumors expressing Gastrin-Releasing Peptide Receptors (GRPrs) - Liolios, Christos; Buchmuller, Benjamin; Bauder-Wüst, Ulrike; Schäfer, Martin; Leotta, Karin; Haberkorn, Uwe; Eder, Matthias; Kopka, Klaus (Journal of medicinal chemistry, 2018)
The GRPr, highly expressed in prostate PCa and breast cancer BCa, is a promising target for the development of new PET radiotracers. The chelator HBED-CC (N,N′-bis[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine-N,N′-diacetic acid) was coupled to the bombesin peptides: HBED-C-BN(2-14) 1, HBED-CC-PEG2-[d-Tyr6,β-Ala11,Thi13,Nle14]-BN(6-14) 2, HBED-CC-Y-[d-Phe6,Sta13,Leu14]-BN(6-14) (Y = 4-amino-1-carboxymethylpiperidine) 3, and HBED-CC-{PEG2-Y-[d-Phe6,Sta13,Leu14]-BN(6-14)}2 4 (homodimer). Compounds 1-4 presented high binding affinities for GRPr (T47D, 0.56-3.51 nM; PC-3, 2.12-4.68 nM). In PC-3 and T47D cells, agonists [68Ga]1 and [68Ga]2 were mainly internalized while antagonists [68Ga]3 and [68Ga]4 were surface bound. Cell-related radioactivity reached a maximum after 45 min, while tracer levels followed GRPr expression (PC-3 > T47D > LNCaP > MDA-MB-231). [68Ga]4 showed the highest cell-bound radioactivity (PC-3 and T47D). In vivo, tumor (PC-3) targeting for [68Ga]3 and [68Ga]4 increased over time, with dynamic μPET showing clearer tumors images at later time points. [68Ga]3 and [68Ga]4 can be considered suitable PET tracers for imaging PCa and BCa expressing GRPr.
Im Titel ist "68" in 68Ga-labeled hochgestellt
Gesehen am 25.02.2020